Auxin production and plant growth promotion by Microbacterium albopurpureum sp. nov. from the rhizoplane of leafless Chiloschista parishii Seidenf. orchid - Tsavkelova, Elena A.; Volynchikova, Elena A.; Potekhina, Natalia V.; Lavrov, Konstantin V.; Avtukh, Alexander N. (Frontiers in Plant Science, 2024)
A plant-associated aerobic, Gram-positive bacterial strain was isolated from the aerial roots of the leafless epiphytic orchid, Chiloschista parishii Seidenf. According to its morphological and cultural characterization, chemotaxonomy, and phylogenetic analysis, the strain ET2 T belongs to the genus Microbacterium, order Micrococcales, class Actinomycetia. Despite that it shared 16S rRNA gene sequence similarity of 99.79% with Microbacterium kunmingense JXJ CY 27-2 T , so they formed a monophyletic group on phylogenetic trees, the two strains showed clear divergence of their genome sequences. The average nucleotide identity (ANI), average amino acid identity (AAI) and digital DNA-DNA hybridization (dDDH) values of ET2 differed greatly from phylogenetically close JXJ CY 27-2 T .Based on the differences being below the threshold for species similarity, together with the unique chemotaxonomic characteristics, strain ET2 T represents a novel species of the genus Microbacterium, for which the name Microbacterium albopurpurea sp. nov. is proposed, with strain ET2 T (VKPM Ac-2212, VKM Ас-2998) as the type strain. This strain revealed obvious plant growth-promoting activities, including diazotrophy and biosynthesis of tryptophan-dependent auxins (indole-3-acetic and indole-3pyruvic acids). Microbial auxins directly stimulated the rhizogenesis; the ET2 T -inoculated seeds of wheat, cucumber and garden cress showed evident promotion in their growth and development, both under optimal and under cold stress conditions. Several genes, putatively involved in auxin biosynthesis were predicted.